2020
DOI: 10.1159/000505653
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Urinary Calcium and Chitotriosidase in a Cohort of Chronic Sarcoidosis Patients

Abstract: <b><i>Background:</i></b> Calcium metabolism alterations are quite common in sarcoidosis and have been correlated with disease activity. <b><i>Objectives:</i></b> The aim of the study was to investigate the clinical significance of calcium metabolism alterations in patients with chronic sarcoidosis. We paid particular attention to associations with specific disease phenotypes and chitotriosidase (CTO) expression. <b><i>Methods:</i></b> 212… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 22 publications
2
17
0
Order By: Relevance
“…Hypercalciuria and hypercalcemia are quite common anomalies in sarcoidosis patients and need to be addressed to prevent severe complications or chronic organ failure (e.g., ventricular arrhythmia, nephrolithiasis, nephrocalcinosis, chronic renal failure). The clinical features of calcium dysregulation in sarcoidosis have been repeatedly described (2,15,25), as well as its underlying pathophysiological processes: however, there are still many concerns about how it should be treated and monitored (26). The guidelines published recently by the ATS endorsed the utility of assessing calcium metabolism in sarcoidosis, recommending serum calcium testing at diagnosis and follow-up to screen for specific alterations (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypercalciuria and hypercalcemia are quite common anomalies in sarcoidosis patients and need to be addressed to prevent severe complications or chronic organ failure (e.g., ventricular arrhythmia, nephrolithiasis, nephrocalcinosis, chronic renal failure). The clinical features of calcium dysregulation in sarcoidosis have been repeatedly described (2,15,25), as well as its underlying pathophysiological processes: however, there are still many concerns about how it should be treated and monitored (26). The guidelines published recently by the ATS endorsed the utility of assessing calcium metabolism in sarcoidosis, recommending serum calcium testing at diagnosis and follow-up to screen for specific alterations (6).…”
Section: Discussionmentioning
confidence: 99%
“…It has been clearly demonstrated that hypercalciuria and hypercalcemia are reliable negative prognostic factors, being associated with a chronic-persistent disease phenotype, high angiotensin-converting enzyme (ACE) levels, old age, hypergammaglobulinemia, and extrapulmonary sarcoid localizations (particularly in the spleen, bone and kidneys) (12)(13)(14). Our research group recently demonstrated a correlation between hypercalciuria and chitotriosidase concentrations, radiological evidence of severe lung involvement, deterioration of lung function (particularly concerning lung alveolar diffusion) and hepatosplenic disease (15), confirming the potential of this non-invasive and cost-sparing biomarker in routine clinical practice.…”
Section: Introductionmentioning
confidence: 97%
“…In the present study, we evaluated serial changes in chitotriosidase and circulating oncomarkers in a cohort of ILD patients divided into IPF and non-IPF groups. Increased chitotriosidase values have been repeatedly reported in sarcoidosis patients, and may predict clinical course and potential relapse of the disease [ 23 , 24 , 25 , 26 , 27 , 28 ]. As expected, serum chitotriosidase in our non-IPF group was high in relation to the presence of sarcoidosis patients.…”
Section: Discussionmentioning
confidence: 99%
“…The dysregulation of the expression level of TLR2 warrants further investigation of its function on the potential causative agent and pathogenic mechanism of pulmonary sarcoidosis. Altered calcium metabolism, which affects approximately 5% to 25% of sarcoidosis patients, can present as hypercalcemia, hypercalciuria, or kidney stones and have been considered correlating with disease activity (24)(25)(26). Calcium metabolism alteration in sarcoidosis is usually because of increased activity of 1-alpha hydroxylase in macrophages of pulmonary granuloma, resulting in low levels of 25-hydroxyvitamin D and high levels of calcitriol (25).…”
Section: Discussionmentioning
confidence: 99%